High-Gain Power-Efficient Front- and Back-End Designs for a 90 nm Transmit-Reference Receiver. (11th November 2012) - Roy, Apratim
Abstract : A new microwave receiver configuration which transmits reference pulses embedded in data streams for synchronization is analyzed with a 90-nm IBM CMOS standard. A two-stage cascode low-noise amplifier (LNA) is proposed for the receiver front-end which is matched by a passive network to save on power-expensive matching techniques. The amplifier exploits a double-differential topology and achieves a below 4 dB noise figure near the center frequency. The overall 3-dB bandwidth is 3.3 GHz withS 21 peaking up to 20.5 dB in theK -band. The back-end of the receiver is implemented through an adjustable analog window-detection circuit. It avoids the use of control voltage generators and sample-hold (S/H) blocks to save electronic overhead and is simulated with a 0.1 2.0 Gbps pulse stream. The achieved speed-to-power ratio for the back-end has a maximum limit of 266 GHz/W. When compared against simulated results of published literature, the proposed designs show improved performance in terms of small-signal gain, noise, speed, and power dissipation.